2010
DOI: 10.1007/s11829-010-9118-z
|View full text |Cite
|
Sign up to set email alerts
|

Background matching behaviour and pathogen acquisition: plant site preference does not predict the bacterial acquisition efficiency of vectors

Abstract: Many insect-borne pathogens are heterogeneously distributed within their hosts: therefore, a vector's within-plant distribution may be a predictor of its exposure to pathogens. In this study, we set out to quantify plant site preference, in the context of background matching, and investigated its effect on acquisition of a bacterial pathogen by its leafhopper vectors. The two green-coloured species, Graphocephala atropunctata and Draeculacephala minerva, preferred green plant tissue and artificial backgrounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 58 publications
3
22
0
1
Order By: Relevance
“…Initial growth of the microcolony, as measured by quantitative PCR soon after bacterial acquisition from infected plants, has shown that X. fastidiosa multiplies exponentially with a doubling time of 7 to 8 h (Killiny and Almeida 2009b). For the best-studied vector species, G. atropunctata, bacterial populations in vectors usually reach ;10 5 cells/insect several days after acquisition, which has been reproduced in different studies (Killiny and Almeida 2009b;Rashed et al 2011), and suggests that physical space available for colonization on the foregut is limited. Although colony growth could suggest that higher bacterial populations in vectors would lead to higher transmission efficiency, there is no evidence supporting this hypothesis.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Initial growth of the microcolony, as measured by quantitative PCR soon after bacterial acquisition from infected plants, has shown that X. fastidiosa multiplies exponentially with a doubling time of 7 to 8 h (Killiny and Almeida 2009b). For the best-studied vector species, G. atropunctata, bacterial populations in vectors usually reach ;10 5 cells/insect several days after acquisition, which has been reproduced in different studies (Killiny and Almeida 2009b;Rashed et al 2011), and suggests that physical space available for colonization on the foregut is limited. Although colony growth could suggest that higher bacterial populations in vectors would lead to higher transmission efficiency, there is no evidence supporting this hypothesis.…”
Section: Discussionmentioning
confidence: 73%
“…Because copies of the X. fastidiosa genome were correlated to colony forming units on plates, and this bacterium easily forms aggregates, it is possible that the number of cells as determined by qPCR is underestimated. However, this remark remains true for the estimation of the cell number in sharpshooters for which the same technique was used (Killiny and Almeida 2009b;Rashed et al 2011). There may exist other technical limitations as well, but these factors would affect the number of cells, not the shape of the curve representing time after the beginning of the acquisition access period and X. fastidiosa populations in vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, strains not capable of colonizing vectors would be expected to be poorly retained in vectors and consequently have decreasing inoculation efficiencies into artificial diets, while other strains deficient only in early attachment would have a constant transmission rate over time. Following general protocols previously described (19), insects were allowed a 6-h acquisition access period on artificial diets and transferred to sweet basil for up to 96 h, allowing cells to colonize or be washed away from the foregut of vectors on a nonsusceptible host plant of the pathogen. Insects were then transferred to X. fastidiosa-free artificial diet chambers for an inoculation access period of 6 h; 25 individuals were tested for each strain and time period.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, because X. fastidiosa acquisition from plants is correlated to its populations within xylem (18), mutants deficient in plant colonization are unlikely to be acquired by vectors. Recently, a plant-free artificial diet system was developed allowing complete transmission experiments to be performed in the absence of plantassociated confounding factors (3,19). We took advantage of this technological advancement to study X. fastidiosa colonization of vectors and performed a series of experiments that focused on the consequences of mutations to various X. fastidiosa genes to different components of the transmission process.…”
mentioning
confidence: 99%
“…Thus, it is possible that very few colonization events of the precibarium occur given the number of cells or cell aggregates that may be ingested by a vector through feeding on sap from an infected xylem vessel. While few colonization events have been suggested based on microscopy data (Almeida and Purcell 2006), quantitative PCR data indicate that approximately one to five thousand cells can be detected in sharpshooter heads after feeding on infected plant material (Rashed et al 2011). Many of the ingested cells likely do not adhere to the insect cuticle and pass through the digestive tract, and therefore are considered to not be involved in vector colonization and X. fastidiosa transmission to plants.…”
Section: Colonization Of Insect Vectorsmentioning
confidence: 99%